2009
DOI: 10.1515/epoly.2009.9.1.596
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the lignin on thermal degradation and melting behaviour of poly(ethylene terephthalate) based composites

Abstract: Poly(ethylene terephthalate) (PET) has been compounded with lignin (L) by a single-screw extruder. The influence of L presence and its content on the thermal stability of PET has been studied by using thermogravimetric analysis. The experiments carried out in oxidative conditions evidenced the barrier effect of L that interferes to the diffusion of the volatile degradation products to the gas phase and at the same time to the diffusion of the oxygen from the gas phase to the PET matrix. The influence of L on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The study reported by Canetti and Bertini 190 showed that the high thermal stability of PET was compromised in a composite containing 20% (w/w) hydrolytic lignin. However, the authors also showed that when the thermal stability was examined in an atmosphere of air the lignin was oxidized to form a carbon rich char coating on the composite material.…”
Section: Lignin Synthetic Polymer Compositesmentioning
confidence: 99%
“…The study reported by Canetti and Bertini 190 showed that the high thermal stability of PET was compromised in a composite containing 20% (w/w) hydrolytic lignin. However, the authors also showed that when the thermal stability was examined in an atmosphere of air the lignin was oxidized to form a carbon rich char coating on the composite material.…”
Section: Lignin Synthetic Polymer Compositesmentioning
confidence: 99%
“…The in situ reactive compatibilization with SEBS-g-MA also contributes protective char layer formation. Thermal degradation and melting behaviour of PET was investigated by Canetti and Bertini [56]. Hydrolytic lignin was directly blended with PET thermoplastic using a single screw extruder.…”
Section: Lignin-based Intumescence In Synthetic Polymersmentioning
confidence: 99%
“…Up to now, few studies have been published on the fire behavior of polymers containing lignin without flame retardant compounds. In this context, Canetti et al used lignin in polypropylene (PP) and polyethylene terephthalate (PET). , An increase in PP thermal degradation temperature with increasing lignin content was observed and attributed to the interactions occurring between PP and lignin, which lead to the formation of protective surface layer. In the case of PET, lignin was found to affect the overall crystallization of the polymer due to nucleating effect.…”
Section: Introductionmentioning
confidence: 99%